2020
DOI: 10.21037/tlcr-19-413
|View full text |Cite
|
Sign up to set email alerts
|

Microsieves for the detection of circulating tumor cells in leukapheresis product in non-small cell lung cancer patients

Abstract: Background: Circulating tumor cells (CTC) in non-small cell lung cancer (NSCLC) patients are a prognostic and possible therapeutic marker, but have a low frequency of appearance. Diagnostic leukapheresis (DLA) concentrates CTC and mononuclear cells from the blood. We evaluated a protocol using two VyCAP microsieves to filter DLA product of NSCLC patients and enumerate CTC, compared with CellSearch as a gold standard.Methods: DLA was performed in NSCLC patients before starting treatment. DLA product equaling 2×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Vimentin failed to show differences between HMFs and cancer cells, regardless of TGFβ stimulation, at both the gene and protein levels, indicating non-specificity (Supplementary Figure S1B). We confirmed that pan-cytokeratin (pan-CK), a widely used biomarker for CTC identification [23], is specifically expressed in MDA-MB-231 breast cancer cells without any signal in HMFs (Figure 1B). Hence, we selected FAP and ITGA5 as biomarkers to detect CAFs and pan-CK as a marker of tumor cells in the following experiment.…”
Section: Selection Of Biomarkers For Cancer-associated Fibroblasts An...supporting
confidence: 69%
See 2 more Smart Citations
“…Vimentin failed to show differences between HMFs and cancer cells, regardless of TGFβ stimulation, at both the gene and protein levels, indicating non-specificity (Supplementary Figure S1B). We confirmed that pan-cytokeratin (pan-CK), a widely used biomarker for CTC identification [23], is specifically expressed in MDA-MB-231 breast cancer cells without any signal in HMFs (Figure 1B). Hence, we selected FAP and ITGA5 as biomarkers to detect CAFs and pan-CK as a marker of tumor cells in the following experiment.…”
Section: Selection Of Biomarkers For Cancer-associated Fibroblasts An...supporting
confidence: 69%
“…Blood was taken from mice in EDTA tubes, followed by 1% PFA fixation overnight. Then, the blood samples were filtrated through a microsieve platform with a chip pore size of 5 µm (Microsieve, VyCAP) [23]. A similar fixation and permeabilization process was performed, and samples were coincubated with corresponding fluorescently labeled antibodies as mentioned in the Section 2.3, followed by scanning under a Nikon Ti-E automated inverted fluorescence microscope.…”
Section: Blood Collection and Microsieve Filtration Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The high recovery rates obtained for the MetaCell kit in HCT116 and DLD1 cells ( Section 3.2 ) with high cell numbers (~10,000) prompted the investigation of recovery rates using lower CRC cell numbers (10, 100, 500 cells), which is more reflective of the number of CTCs likely to be present in the circulation of CRC patients. The CRC cells from the unfiltered and MetaCell-filtered groups for the different CRC cell numbers were stained with CTC and WBC markers [ 37 ]; cells staining positively for CTC markers and negative for WBC markers were manually counted. For HCT116 cells spiked in blood at 10, 100, and 500, the MetaCell recovery rates were 85.9%, 86.6%, and 87.6%, respectively ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%